The Role Of Attorney In Handling Confiscated Articles Of Criminal Offense In Narcotics: A Case Study Of The Humbang Hasundutan District Attorney Office - Ratih Intan Gayatri; Ediwarman Ediwarman; Marlina Marlina; Wessy Trisna (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Keeping confiscated articles related to criminal offenses involving narcotics that have been marked for destruction may lead to concerns about the potential risk of them being sold again and used by unscrupulous law enforcement officers. In reality, however, confiscated narcotics with their confirmed legal status, court- issued case dispositions, and final and conclusive verdicts, are still retained rather than destroyed, perhaps due to their minimal quantity or due to various obstacles. The authority of prosecutors is regulated in Articles 270 to 276 of the Criminal Procedure Code (KUHAP), Article 30 paragraph (1) letter b of Law No. 11 of 2021 concerning the Indonesian Attorney General's Office, and Article 91 Paragraph 1 of Law No. 35 of 2009 concerning Narcotics which provide authority in determining the status of narcotic items. The role of prosecutors is described in the Indonesian Attorney General's Office Standard Operating Procedure No. 2 of 2022 in Chapter III which includes recording, research, storage, maintenance, security, provision, return, and resolution of confiscated items. Internal and external obstacles are faced, but preventive and repressive efforts have been undertaken. Efforts are focused on resolving internal and external factors in handling narcotics evidence. The importance of the prosecutor's role in handling narcotics evidence is highlighted, emphasizing the need for more effective efforts to overcome obstacles for improvement in future handling.